#TITLE_ALTERNATIVE# - NUR ROHIM (NIM : 10210077), GINANJAR
Physics can be used as a basic for other knowledge to undeerstand the phenomena that exist, including the problems in economics and finance. This branch of knowledge is well known as Econophysics. Econophysics can be used in the optimization portfolio formation using Random Matrix Theory (RMT), which was originally used in nuclear physics. RMT filtering the randomness (noise) that appears when forming the portfolio using a correlation matrix (C). Portfolio formed using sharia stock listed on the Jakarta Islamic Index (JII) in the period 2011-2014. Sharia stock portfolio were compared for itÃ‚Â’s performance with Sharia Equity Fund (SEF) based on stock selection using Sharpe and Treynor method. SEF performance was monitored in the period 2011-2014 that divided by three periods based on the state of sharia stock market. Bullish sharia stock market (2011-2012), sharia stock market crash (2013), and sharia stock market rebound (2014). The formation of sharia stocks portfolio with RMT method has good performance when there is stable fluctuations (volatility) of sharia stock market.